Neem in dentistry - a review - Hassan, Shaik Ali; Prathyusha, Francis; Bhateja, Sumit; Arora, Geetika (Indian Journal of Integrative Medicine, 2021)
Background: Since days neem has been utilized by Indian individuals for treatment of different ailments because of its therapeutic properties. Objective: The aim of the study to evaluate how the neem has a beneficial effect on dental diseases. Methods: Pubmed and Google Scholar were searched for relevant information regarding Neem and its uses. Results: Total 31 articles were selected for review which included information about the uses of Neem and its effects. Conclusion: It is an attempt to become familiar with the old Indian ways, which can be used to reduce most of the dental problems. It can be used better than the allopathic drugs as it doesn't contain any side effects.